Malaysian cultural assets: a collection of Sabah ethnic Batik - Noorhayati Mansor; Bamini Kpd Balakrishnan; Ruth S. Siganul; Roseni Ariffin (Universiti Malaysia Sabah, 2010)
This research attempts to document traditional ethnic motifs of the dominant ethnic groups in Sabah. Unlike motifs of other ethnic communities, the Sabah ethnic motifs carry specific meanings and must be presented in specific manners. These motifs are now being incorporated in batik designs to create unique and innovative identities of Sabah batik. Batik refers to a traditional technique of using wax as a dye-repellent to hand-dye fabrics. Unlike the states of Kelantan and Terengganu in Peninsular Malaysia which are well known for their small-scale batik industry, Sabah entrepreneurs appear to avoid the batik business. In general, the Indonesian batik seems to dominate the Borneo markets. To date, the Malaysian batik Industry continues to demonstrate a high growth potential. For the year 2008, the Malaysian batik recorded more than a three-fold increased in export sales (New Straits Times, 21 March 2009). The recent plan by the Ministry of Tourism to establish trading houses for batik in Europe also suggests a healthy growth in international demand. However, a review of published work suggests that research interest in the Malaysian batik industry is still at its infancy, particularly in the states of Sabah and Sarawak. With the potential for the ethnic batik industry to penetrate the international fashion Industry, it is crucial to address the history and document the local collection of ethnic batik in Sabah. It is well known that the local ethnic batik producers are mostly owner-operated, traditionally-managed, relatively small in size and also new in the business of international marketing. Existing research on small firm has studied the marketing activity largely on the observed behavioral issues (e.g., Hannon and Atherthon, 1998; Smith and Whittaker, 1998; and Huang and Brown, 1999). The research benefits from an official collaboration with a local batik entrepreneur who contributes her expertise and batik designs to the project. This project enriches our understanding of Malaysian cultural assets by documenting the ethnic batik designs in a coffee-table book which can be commercialised as one of tourism products of Malaysia.